2017
DOI: 10.1590/0100-29452017699
|View full text |Cite
|
Sign up to set email alerts
|

PHENOTYPIC VARIABILITY IN FEIJOA FRUITS [Acca sellowiana (O. Berg.) Burret] ON INDIGENOUS LANDS,QUILOMBOLAS COMMUNITIES AND PROTECTED AREAS IN THE SOUTH OF BRAZIL

Abstract: -Phenotypic studies with native fruits are important sources of information for understanding the status of conservation of plant species, especially populations in protected areas (Pas). Fruits of 18 populations of feijoa [Acca sellowiana (O. Berg.) Burret] present in three kind of Pas, Quilombolas communities (QLs), Indigenous Lands (ILs) and conservation units (cus) were evaluated with the aim to characterize the phenotypic variability. Fruits were harvested at maturity and eight morphological descriptors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 9 publications
3
20
0
Order By: Relevance
“…These results had greater amplitude compared with the data found by Degenhardt et al (2003), who evaluated two half-sib families and found pulp yields in progenies ranging from 23.5 to 33.7%. In natural populations, mean values for pulp yield ranged from 17.3 to 49.5% (Borsuk et al, 2017).…”
Section: Maxmentioning
confidence: 99%
See 1 more Smart Citation
“…These results had greater amplitude compared with the data found by Degenhardt et al (2003), who evaluated two half-sib families and found pulp yields in progenies ranging from 23.5 to 33.7%. In natural populations, mean values for pulp yield ranged from 17.3 to 49.5% (Borsuk et al, 2017).…”
Section: Maxmentioning
confidence: 99%
“…The species occurs naturally in the highlands of Paraná and Santa Catarina and in Rio Grande do Sul, Brazil (Mattos, 1986;Donazzolo, 2012;Borsuk et al, 2017), in the Departments Treinta y Tres (Quebrada de los Cuervos), Cerro Largo (Cañitas), and Tacuarembó (Valle Edén and Cuchilla de Laureles), north of Uruguay (Puppo et al, 2014). The feijoa active germplasm bank (BAG) is located in São Joaquim, Santa Catarina State, in the south of Brazil.…”
mentioning
confidence: 99%
“…In addition, the 12 accessions identified as “Exterior” in this study originated from four countries (Supplemental Table S1) and are genotypes of Uruguay type, with a narrow genetic base, as previously reported (Dettori & Palombi, 2000; Ducroquet et al., 2000; Nodari et al., 1997; Thorp & Bieleski, 2002). Other studies detected lower genetic (Donazzolo et al., 2020) and phenotypic diversity (Borsuk et al., 2017; Sánchez‐Mora et al., 2019) in the Uruguay type compared with the Brazil type. Furthermore, the genetic distances amongst the Uruguay type accessions are smaller compared with the Brazil type accessions, as documented in the present study and by previous studies (Borsuk, 2018; Donazzolo, 2012; Donazzolo et al., 2020).…”
Section: Discussionmentioning
confidence: 87%
“…Other studies detected lower genetic (Donazzolo et al, 2020) and phenotypic diversity (Borsuk et al, 2017;Sánchez-Mora et al, 2019) in the Uruguay type compared with the Brazil type. Furthermore, the genetic distances amongst the Uruguay type accessions are smaller compared with the Brazil type accessions, as documented in the present study and by previous studies (Borsuk, 2018;Donazzolo, 2012;Donazzolo et al, 2020).…”
Section: Missing In Agb-feijoamentioning
confidence: 77%
See 1 more Smart Citation